2019
DOI: 10.1024/1662-9647/a000210
|View full text |Cite
|
Sign up to set email alerts
|

Tablet-Based Outpatient Care for People With Dementia

Abstract: Abstract. Most people with dementia (PwD) are treated on an outpatient basis, predominantly by general practitioners (GPs). This article provides a detailed protocol of a study aimed at developing and evaluating a tablet-based intervention to improve outpatient dementia care by fostering guideline-based treatment. A cluster-randomized controlled trial with an intervention group (tablet-based intervention) and a control group (treatment as usual plus information handbook) will be conducted. Clusters will be ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 39 publications
0
17
0
2
Order By: Relevance
“…The trial is currently ongoing. A more detailed description of study design, sampling methods, variables and procedures can be found in Lech et al [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The trial is currently ongoing. A more detailed description of study design, sampling methods, variables and procedures can be found in Lech et al [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…A study protocol of the DemTab study was published elsewhere (35). The study was conducted and reported in accordance with the CONSORT guidelines for cRCT and ethical approval was obtained by the ethics committee of the Charité -Universitätsmedizin Berlin (EA1/085/19).…”
Section: Methodsmentioning
confidence: 99%
“…Secondary outcomes include various health outcomes assessed in PwD (e.g., quality of life) and caregivers (e.g., caregiver burden). An overview of assessments can be found elsewhere (35). A cluster-randomisation of GPs was conducted as a covariate-constrained randomisation with the package cvcrand (RefNum) using the statistics software R (RefNum).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Auf Grundlage einer Recherche zur Akzeptanz im Kontext der Technologieanwendung wurde ein Interviewleitfaden entwickelt, der durch die Konsultation zweier Forscher aus dem Bereich Pflegewissenschaft sowohl aus inhaltlicher als auch aus methodischer Perspektive qualitativ abgesichert wurde (Helfferich 2011 mehreren Iterationsschleifen fallbezogen, um so das Verständnis des Textes auszubauen und Bedeutungen erschließen zu können. Anschließend fand die fallübergreifende Auswertung statt, bei der zentrale Themen und Aspekte in einem induktiv erstellten Kategoriensystem dargestellt werden (Döring und Bortz 2016).…”
Section: Interview Und Datenauswertungunclassified
“…In einer sich noch in der Auswertung befindlichen Cluster-randomisierten Studie, die ein selbstentwickeltes Tablet zur Biografiearbeit einsetzt, deuten erste Ergebnisse auf eine Verbesserung der Ergebnisparameter Glück, Stimmung und Sozialverhalten hin (Nordheim et al 2017;Lech et al 2019). Eine weitere explorative Studie, bei der ein Tablet zur Biografierecherche und -erinnerung in 6 Einzelsitzungen je Teilnehmer eingesetzt wurde, konnte die Zunahme der Zufriedenheit der Teilnehmer und eine Abnahme des Problemverhaltens beobachten (Dlugosch 2015).…”
Section: Introductionunclassified